INVESTIGATION OF THE RELATIONSHIP BETWEEN THE STUDENTS' ACHIEVEMENT IN THE RELIGIOUS CULTURE AND ETHICS KNOWLEDGE COURSE AND ATTITUDES OF PARENTS TOWARDS THE TEACHER OF THE COURSE - Muhammet Mustafa BAYRAKTAR (Fırat University, 2019)
It is known that there are many factors that influence students' academic achievement in general and their achievements in Religious Culture and Ethics Knowledge course in particular. In order for the goals, aims and achievements in the Religious Culture and Ethics Knowledge course to be realized, it is important to reveal these factors and determine the relations between them. In this respect, we tried to determine how parents' attitudes towards the teacher of the Religious Culture and Ethics Knowledge course are related to their children's achievements in the course in our research. The population of the research consists of parents of the students enrolled in primary schools affiliated to the Ministry of National Education in Van in 2003-2004 academic year. The prepared questionnaire was applied to the sample consisting of parents of the 4th and 8th grade students in 11 schools. In our research, hypothesis testing was based on a minimum of .05 significance level for the difference between relationships. It is thought that our research will reveal how parental attitudes towards the teachers of the Religious Culture and Ethics Knowledge course influence students' achievement in Religious Culture and Ethics Knowledge courses and also contribute to the studies on Religious Culture and Ethics Knowledge course achievements in Turkey.